Bacterial Toxins as Pathogen Weapons Against Phagocytes - do Vale, Ana; Cabanes, Didier; Sousa, Sandra (Frontiers in Microbiology, 2016)
Bacterial toxins are virulence factors that manipulate host cell functions and take over the control of vital processes of living organisms to favour microbial infection. Some toxins directly target innate immune cells, thereby annihilating a major branch of the host immune response. In this review we will focus on bacterial toxins that act from the extracellular milieu and hinder the function of macrophages and neutrophils. In particular, we will concentrate on toxins from Gram-positive and Gram-negative bacteria that manipulate cell signalling or induce cell death by either imposing direct damage to the host cells cytoplasmic membrane or enzymatically modifying key eukaryotic targets. Outcomes regarding pathogen dissemination, host damage and disease progression will be discussed.